APPLICATION OF ISLAMIC FAMILY LAW TO THE MUSLIM MINORITY OF SOUTH PATANI THAILAND - Agustar, Armi; Nurcahaya (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2024)
Abstract This article examines the application of Islamic family law to the Muslim minority in Thailand's Southern Patani, a region dominated by secular national law and where the majority of the population is Buddhist. The Patani Muslim Community implements Islamic family law in aspects of marriage, divorce, inheritance and child custody in accordance with the teachings of the Shari'a and local customs. The wedding procession includes the marriage contract, dowry, and walimatul urus. However, this community faces challenges such as conflicts between Islamic law and national law, inconsistent legal recognition, and the impact of modernization. Nevertheless, they try to maintain traditions with education, outreach, and cooperation with authorities. Government support and increased intercultural dialogue are critical to ensuring justice and social harmony in Patani.